Preparation method of tundish permanent layer refractory material for thin-strip cast-rolling short-process steelmaking
By generating polydopamine on the surface of ZrO2/carbon-coated fibers and reacting it with amino-terminated polyborosiloxane, the problem of weak fiber-matrix bonding in traditional intermediate liner permanent layer materials was solved, achieving fiber stability and toughening effect at high temperatures, and improving the fire resistance and mechanical properties of the material.
Patent Information
- Application Number
- CN202511111925.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-10-21
AI Technical Summary
Traditional intermediate liner permanent layer materials have weak bonding between fibers and the matrix at high temperatures, leading to interfacial delamination and reducing the toughening effect of the fibers.
Polydopamine is generated by self-polymerization on the surface of ZrO2/carbon-coated fibers, and then covalently grafted with terminal amino-terminated polyborosiloxane through Schiff base reaction, which improves the interfacial compatibility and stability between the fiber and the matrix, forming a continuous and dense protective film.
It enhances the bonding force between the fiber and the matrix, improves the fire resistance and mechanical properties of the material, avoids fiber peeling and oxidation at high temperatures, and ensures the uniformity and toughening effect of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of refractory materials, in particular to a method for preparing a tundish permanent layer refractory material for thin strip casting and rolling short-process steelmaking. Background Art
[0002] The tundish is a critical piece of equipment in the continuous casting process, and its permanent refractory layer must withstand long-term exposure to high-temperature molten steel, thermal shock, and chemical attack. Traditionally, refractory materials refer to inorganic, non-metallic materials with a refractoriness of at least 1580°C. They serve as the foundation for high-temperature technologies, serving as structural materials for thermal equipment such as high-temperature kilns, as well as for industrial high-temperature vessels and components. They must also withstand the corresponding physical and chemical changes and mechanical forces.
[0003] Traditional tundish permanent layer materials (such as high-alumina and aluminum silicate) have the following issues: 1. Insufficient thermal shock resistance: Rapid temperature changes can cause crack propagation and material spalling. 2. Poor corrosion resistance: Components such as CaO and FeO in molten steel and slag easily corrode the material matrix, shortening its service life.
[0004] Patent CN106336228B provides a composite fiber-toughened refractory material and its preparation process. The refractory material of this patent is made of raw materials such as alumina-silicon oxide mixed powder, calcium oxide, magnesium oxide, manganese oxide, titanium oxide, niobium pentoxide and toughening fiber. The invention adds titanium metal fiber to the toughening fiber, which enhances the fracture toughness and thermal shock resistance of the refractory material under medium and low temperature conditions; modified zirconium oxide fiber is added to the toughening fiber, which improves the fracture toughness and thermal shock resistance of the refractory material under high temperature conditions, and makes up for the deficiency of poor high-temperature fracture toughness when only titanium metal fiber is added. However, the bonding force between the refractory matrix material and the fiber in this patent is weak, and interface peeling is prone to occur at high temperature, which reduces the toughening effect of the fiber. Summary of the Invention
[0005] The present invention provides a method for preparing a permanent layer refractory material for a tundish used in a short-process steelmaking process of thin strip casting and rolling, which can solve the problem in the background technology that the bonding force between the refractory matrix material and the fiber is weak, interface peeling is easy to occur at high temperature, and the toughening effect of the fiber is reduced.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a tundish permanent layer refractory material for a thin strip casting and rolling short process steelmaking process comprises the following steps: S1, preparing ZrO2 / carbon wrapped fibers; S2. Dissolve dopamine hydrochloride in Tris-HCl buffer (pH = 8.5), stir for 4-8 minutes, then add ZrO2 / carbon-coated fibers, soak at room temperature for 6-8 hours, wash, and dry to obtain PDA / ZrO2 / carbon-coated fibers; The dosage ratio of dopamine hydrochloride, Tris-HCl buffer, and ZrO2 / carbon-wrapped fiber is 0.1-0.2 g:100 mL:2 g.
[0007] In the above steps, dopamine hydrochloride self-polymerizes on the surface of ZrO2 / carbon-coated fibers in a weakly alkaline environment to generate polydopamine.
[0008] S3, dissolving amino-terminated polyborosiloxane in anhydrous ethanol, soaking the PDA / ZrO2 / carbon-wrapped fiber in the anhydrous ethanol for 6-8 hours, washing, and drying to obtain a composite fiber; The usage ratio of amino-terminated polyborosiloxane, anhydrous ethanol, and PDA / ZrO2 / carbon-wrapped fiber is 0.15-0.2 g: 80-100 mL: 2 g.
[0009] Dopamine quinone is produced during the oxidative polymerization of dopamine, which can undergo a Schiff base reaction with the amino group of amino-terminated polyborosiloxane to obtain composite fibers.
[0010] S4. Put magnesia spinel, nano-alumina, fused chromium oxide, boron carbide, white dextrin and anhydrous ethanol into a ball mill and mix them by ball milling for 2 hours to obtain a ball-milled product; after drying the ball-milled product, mix it evenly with the composite fiber, and then dry-press it under a pressure of 15 MPa to obtain a green body; sinter the green body and cool it to room temperature to obtain the refractory material for the permanent layer of the tundish.
[0011] The mass ratios of magnesia spinel, nano-alumina, fused chromium oxide, boron carbide, white dextrin, anhydrous ethanol and composite fiber are (40-48): (20-22): (10-15): (1-4): (1.5-2): (60-70): (8-12).
[0012] Furthermore, in step S1, the specific preparation steps of ZrO2 / carbon-wrapped fibers are as follows: A1: Polycrystalline alumina fibers were immersed in a glucose aqueous solution with a pH of 1.5-2, transferred to an autoclave after ultrasonic treatment, sealed, and evacuated to a vacuum of 0.08 MPa. After standing for 1-2 hours, the vacuum was broken to atmospheric pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min, held at that temperature for 4 hours, and then cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fibers. The usage ratio of the polycrystalline alumina fiber and the glucose aqueous solution is 1 g: 80-100 mL; and the mass concentration of the glucose aqueous solution is 17 wt%-20 wt%.
[0013] A2: After evenly mixing anhydrous ethanol and 24wt% hydrogen peroxide, zirconium oxychloride octahydrate was added with stirring, and acetylacetone was added after continued stirring to obtain a sol treatment solution; the carbon-wrapped fiber was added into the sol treatment solution, immersed for 50-60 minutes, and the solid was separated. After drying to constant weight, the solid was transferred into a calcining furnace, and heated to 820°C at a heating rate of 4°C / min in an argon atmosphere. The fiber was kept warm and calcined for 3 hours, and then cooled to room temperature to obtain ZrO2 / carbon-wrapped fiber.
[0014] The usage ratio of anhydrous ethanol, hydrogen peroxide, zirconium oxychloride octahydrate, and acetylacetone is 7 mL: 50 mL: 8-9 g: 1.2 g; and the usage ratio of carbon-wrapped fiber and sol treatment liquid is 1 g: 50-60 mL.
[0015] Furthermore, in step S3, the preparation method of amino-terminated polyborosiloxane is: Ethyl orthosilicate, boric acid and deionized water were weighed and added to an 80% by volume ethanol aqueous solution, heated to 80°C, and dilute hydrochloric acid was added and reacted for 3 h. 3-aminopropyltrimethoxysilane was then added and reacted for 3 h. The mixture was kept warm and subjected to reduced pressure distillation to remove water and ethanol. After vacuum drying, amino-terminated polyborosiloxane was obtained.
[0016] The usage ratio of ethyl orthosilicate, boric acid, deionized water, ethanol aqueous solution, dilute hydrochloric acid and 3-aminopropyltrimethoxysilane is 4.1 g: 0.6 g: 1-2 mL: 10 mL: 0.05 g: 2.7-3.6 g.
[0017] Furthermore, in step S4, the sintering temperature is 1250-1350° C., and the sintering time is 2-3 hours.
[0018] Beneficial effects of the present invention: 1. The present invention coats the surface of ZrO2 / carbon-coated fibers with a layer of polydopamine. Dopamine quinone then reacts with the amino groups of amino-terminated polyborosiloxane via a Schiff base reaction to produce a composite fiber. Polydopamine exhibits strong adhesion, improving interfacial compatibility between the composite fiber and the refractory matrix (such as magnesia-iron spinel and nano-alumina). Polydopamine further reacts with the amino-terminated polyborosiloxane, and its chain segments reduce interfiber aggregation through steric hindrance. This more uniform dispersion enables the fibers to form a more effective "reinforcement network" within the refractory material, avoiding stress concentration caused by localized fiber accumulation or weak areas caused by localized fiber loss. This ensures uniform material properties, facilitates the fibers' toughening effect, and improves the material's fire resistance and other properties.
[0019] 2. Amino-terminated polyborosiloxane molecules contain BO and Si-O bonds, which have high bond energies and excellent high-temperature and oxidation resistance. After grafting, it forms a protective layer on the fiber surface. During sintering and subsequent use, it inhibits oxidation of the carbon phase in the composite fiber, preventing the collapse of the fiber structure. It also forms a continuous, dense protective film on the fiber surface, maintaining the fiber's toughening effect.
[0020] 3. Unlike physical adsorption (e.g., simple immersion adsorption), the Schiff base reaction forms a covalent bond with high bond energy and strong stability. This allows the amino-terminated polyborosiloxane to be firmly grafted onto the PDA coating surface. During the subsequent ball milling, dry pressing, and high-temperature sintering processes, it is not easily detached due to mechanical forces or heat, thus ensuring the effectiveness of the modified layer throughout the entire refractory preparation process. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0022] The polycrystalline alumina fiber of the present invention has an alumina content of 90 wt %, a fiber diameter of 4 μm, and a fiber length of 65 mm.
[0023] Example 1
[0024] A method for preparing a tundish permanent layer refractory material for a thin strip casting and rolling short process steelmaking process comprises the following steps: S1. 1 g of polycrystalline alumina fiber was immersed in 80 mL of a glucose aqueous solution with a pH of 1.5-2 and a mass concentration of 17 wt %. The solution was transferred to an autoclave after ultrasonication. The autoclave was sealed and evacuated to a vacuum degree of 0.08 MPa. After standing for 1 h, the vacuum was broken to normal pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min. The temperature was maintained for 4 h, and the autoclave was cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fiber. S2. After uniformly mixing 7 mL of anhydrous ethanol and 50 mL of 24 wt% hydrogen peroxide, add 8 g of zirconium oxychloride octahydrate while stirring, continue stirring, add 1.2 g of acetylacetone, and stir to obtain a sol treatment solution; add 1 g of carbon-wrapped fiber into 50 mL of the sol treatment solution, soak for 50 minutes, separate the solid, dry to constant weight, and transfer into a calcining furnace. In an argon atmosphere, heat up to 820°C at a heating rate of 4°C / min, keep warm and calcine for 3 hours, and cool to room temperature to obtain ZrO2 / carbon-wrapped fiber.
[0025] S3, dissolving 0.1 g of dopamine hydrochloride in 100 mL of Tris-HCl buffer (pH = 8.5), stirring for 4 min, then adding 2 g of ZrO2 / carbon-wrapped fiber, soaking at room temperature for 6 h, washing, and drying to obtain PDA / ZrO2 / carbon-wrapped fiber; S4, dissolving 0.15 g of amino-terminated polyborosiloxane in 80 mL of anhydrous ethanol, soaking 2 g of PDA / ZrO2 / carbon-wrapped fiber in the solution for 6 h, washing, and drying to obtain a composite fiber; S5. Put 40g of magnesia spinel, 20g of nano-alumina, 10g of fused chromium oxide, 1g of boron carbide, 1.5g of white dextrin and 60g of anhydrous ethanol into a ball mill and mix them by ball milling for 2h to obtain a ball-milled material; after drying the ball-milled material, mix it evenly with 8g of composite fiber, and then dry-press it under a pressure of 15MPa to obtain a green body; transfer the green body into a sintering furnace, sinter it at 1300℃ for 2h, and cool it to room temperature to obtain the refractory material for the permanent layer of the tundish.
[0026] The preparation method of amino-terminated polyborosiloxane is as follows: Weigh 4.1 g of ethyl orthosilicate, 0.6 g of boric acid, and 2 mL of deionized water, add them to 10 mL of 80% ethanol aqueous solution, heat to 80°C, add 0.05 g of dilute hydrochloric acid, react for 3 h, then add 2.7 g of 3-aminopropyltrimethoxysilane, react for 3 h, keep warm, distill under reduced pressure to remove water and ethanol, and vacuum dry to obtain amino-terminated polyborosiloxane.
[0027] Example 2
[0028] A method for preparing a tundish permanent layer refractory material for a thin strip casting and rolling short process steelmaking process comprises the following steps: S1. 1 g of polycrystalline alumina fiber was immersed in 90 mL of a glucose aqueous solution with a pH of 1.5-2 and a mass concentration of 18 wt %. The solution was transferred to an autoclave after ultrasonication. The autoclave was sealed and evacuated to a vacuum degree of 0.08 MPa. After standing for 2 h, the vacuum was broken to normal pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min. The temperature was maintained for 4 h, and the autoclave was cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fiber. S2. After uniformly mixing 7 mL of anhydrous ethanol and 50 mL of 24 wt% hydrogen peroxide, add 9 g of zirconium oxychloride octahydrate while stirring, continue stirring, add 1.2 g of acetylacetone, and stir to obtain a sol treatment solution; add 1 g of carbon-wrapped fiber into 60 mL of the sol treatment solution, soak for 60 minutes, separate the solid, dry to constant weight, and transfer into a calcining furnace. In an argon atmosphere, heat up to 820°C at a heating rate of 4°C / min, keep warm and calcine for 3 hours, and cool to room temperature to obtain ZrO2 / carbon-wrapped fiber.
[0029] S3, dissolving 0.15 g of dopamine hydrochloride in 100 mL of Tris-HCl buffer (pH = 8.5), stirring for 8 min, then adding 2 g of ZrO2 / carbon-wrapped fiber, soaking at room temperature for 8 h, washing, and drying to obtain PDA / ZrO2 / carbon-wrapped fiber; S4, dissolving 0.2 g of amino-terminated polyborosiloxane in 100 mL of anhydrous ethanol, soaking 2 g of PDA / ZrO2 / carbon-wrapped fiber in the solution for 8 h, washing, and drying to obtain a composite fiber; S5. Put 44g of magnesia spinel, 21g of nano-alumina, 12.5g of fused chromium oxide, 2.5g of boron carbide, 1.7g of white dextrin and 65g of anhydrous ethanol into a ball mill and mix them by ball milling for 2h to obtain a ball-milled material; after drying the ball-milled material, mix it evenly with 9g of composite fiber, and then dry-press it under a pressure of 15MPa to obtain a green body; transfer the green body into a sintering furnace, sinter it at 1300℃ for 2h, and cool it to room temperature to obtain the refractory material for the permanent layer of the tundish.
[0030] The preparation method of amino-terminated polyborosiloxane is as follows: Weigh 4.1 g of ethyl orthosilicate, 0.6 g of boric acid, and 2 mL of deionized water, add them to 10 mL of 80% ethanol aqueous solution, heat to 80°C, add 0.05 g of dilute hydrochloric acid, react for 3 h, then add 3.6 g of 3-aminopropyltrimethoxysilane, react for 3 h, keep warm, distill under reduced pressure to remove water and ethanol, and vacuum dry to obtain amino-terminated polyborosiloxane.
[0031] Example 3
[0032] A method for preparing a tundish permanent layer refractory material for a thin strip casting and rolling short process steelmaking process comprises the following steps: S1. 1 g of polycrystalline alumina fiber was immersed in 100 mL of a 20 wt% glucose aqueous solution with a pH of 1.5-2. After ultrasonication, the fiber was transferred to an autoclave, which was sealed and evacuated to a vacuum degree of 0.08 MPa. After standing for 2 h, the vacuum was broken to normal pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min, kept at this temperature for 4 h, and then cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fiber. S2. After uniformly mixing 7 mL of anhydrous ethanol and 50 mL of 24 wt% hydrogen peroxide, add 9 g of zirconium oxychloride octahydrate while stirring, continue stirring, add 1.2 g of acetylacetone, and stir to obtain a sol treatment solution; add 1 g of carbon-wrapped fiber into 60 mL of the sol treatment solution, soak for 60 minutes, separate the solid, dry to constant weight, and transfer into a calcining furnace. In an argon atmosphere, heat up to 820°C at a heating rate of 4°C / min, keep warm and calcine for 3 hours, and cool to room temperature to obtain ZrO2 / carbon-wrapped fiber.
[0033] S3, dissolving 0.2 g of dopamine hydrochloride in 100 mL of Tris-HCl buffer (pH = 8.5), stirring for 8 min, then adding 2 g of ZrO2 / carbon-wrapped fiber, soaking at room temperature for 8 h, washing, and drying to obtain PDA / ZrO2 / carbon-wrapped fiber; S4, dissolving 0.2 g of amino-terminated polyborosiloxane in 100 mL of anhydrous ethanol, soaking 2 g of PDA / ZrO2 / carbon-wrapped fiber in the solution for 8 h, washing, and drying to obtain a composite fiber; S5. Put 48g of magnesia spinel, 22g of nano-alumina, 15g of fused chromium oxide, 4g of boron carbide, 2g of white dextrin and 70g of anhydrous ethanol into a ball mill and mix them by ball milling for 2h to obtain a ball-milled material; after drying the ball-milled material, mix it evenly with 10g of composite fiber, and then dry-press it under a pressure of 15MPa to obtain a green body; transfer the green body into a sintering furnace, sinter it at 1300℃ for 2h, and cool it to room temperature to obtain the refractory material for the permanent layer of the tundish.
[0034] The preparation method of amino-terminated polyborosiloxane is as follows: Weigh 4.1 g of ethyl orthosilicate, 0.6 g of boric acid, and 2 mL of deionized water, add them to 10 mL of 80% ethanol aqueous solution, heat to 80°C, add 0.05 g of dilute hydrochloric acid, react for 3 h, then add 3.6 g of 3-aminopropyltrimethoxysilane, react for 3 h, keep warm, distill under reduced pressure to remove water and ethanol, and vacuum dry to obtain amino-terminated polyborosiloxane.
[0035] Example 4
[0036] The only difference between this embodiment and embodiment 3 is that "10 g of composite fiber" in step S5 of embodiment 3 is replaced by "11 g of composite fiber".
[0037] Example 5
[0038] The only difference between this embodiment and embodiment 3 is that "10 g of composite fiber" in step S5 of embodiment 3 is replaced by "12 g of composite fiber".
[0039] Comparative Example 1
[0040] This comparative example is different from Example 1 only in that the amino-terminated polyborosiloxane is omitted. The specific steps are as follows: S1. 1 g of polycrystalline alumina fiber was immersed in 80 mL of a glucose aqueous solution with a pH of 1.5-2 and a mass concentration of 17 wt %. The solution was transferred to an autoclave after ultrasonication. The autoclave was sealed and evacuated to a vacuum degree of 0.08 MPa. After standing for 1 h, the vacuum was broken to normal pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min. The temperature was maintained for 4 h, and the autoclave was cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fiber. S2. After uniformly mixing 7 mL of anhydrous ethanol and 50 mL of 24 wt% hydrogen peroxide, add 8 g of zirconium oxychloride octahydrate while stirring, continue stirring, add 1.2 g of acetylacetone, and stir to obtain a sol treatment solution; add 1 g of carbon-wrapped fiber into 50 mL of the sol treatment solution, soak for 50 minutes, separate the solid, dry to constant weight, and transfer into a calcining furnace. In an argon atmosphere, heat up to 820°C at a heating rate of 4°C / min, keep warm and calcine for 3 hours, and cool to room temperature to obtain ZrO2 / carbon-wrapped fiber.
[0041] S3, dissolving 0.1 g dopamine hydrochloride in 100 mL Tris-HCl buffer (pH = 8.5), stirring for 4 min, then adding 2 g ZrO2 / carbon-coated fiber, soaking at room temperature for 6 h, washing, and drying to obtain composite fiber; S4. Put 40g of magnesia spinel, 20g of nano-alumina, 10g of fused chromium oxide, 1g of boron carbide, 1.5g of white dextrin and 60g of anhydrous ethanol into a ball mill, and mix them by ball milling for 2h to obtain a ball-milled material; after drying the ball-milled material, mix it evenly with 8g of composite fiber, and then dry-press it under a pressure of 15MPa to obtain a green body; transfer the green body into a sintering furnace, sinter it at 1300℃ for 2h, and cool it to room temperature to obtain the refractory material of the permanent layer of the tundish.
[0042] Comparative Example 2
[0043] This comparative example is different from Example 1 only in that amino-terminated polyborosiloxane and PDA are omitted. The specific steps are as follows: S1. 1 g of polycrystalline alumina fiber was immersed in 80 mL of a glucose aqueous solution with a pH of 1.5-2 and a mass concentration of 17 wt %. The solution was transferred to an autoclave after ultrasonication. The autoclave was sealed and evacuated to a vacuum degree of 0.08 MPa. After standing for 1 h, the vacuum was broken to normal pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min. The temperature was maintained for 4 h, and the autoclave was cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fiber. S2. After uniformly mixing 7 mL of anhydrous ethanol and 50 mL of 24 wt% hydrogen peroxide, add 8 g of zirconium oxychloride octahydrate while stirring, continue stirring, add 1.2 g of acetylacetone, and stir to obtain a sol treatment solution; add 1 g of carbon-wrapped fiber into 50 mL of the sol treatment solution, soak for 50 minutes, separate the solid, dry to constant weight, and transfer into a calcining furnace. In an argon atmosphere, heat up to 820°C at a heating rate of 4°C / min, keep warm and calcine for 3 hours, and cool to room temperature to obtain a composite fiber.
[0044] S4. Put 40g of magnesia spinel, 20g of nano-alumina, 10g of fused chromium oxide, 1g of boron carbide, 1.5g of white dextrin and 60g of anhydrous ethanol into a ball mill, and mix them by ball milling for 2h to obtain a ball-milled material; after drying the ball-milled material, mix it evenly with 8g of composite fiber, and then dry-press it under a pressure of 15MPa to obtain a green body; transfer the green body into a sintering furnace, sinter it at 1300℃ for 2h, and cool it to room temperature to obtain the refractory material of the permanent layer of the tundish.
[0045] Comparative Example 3
[0046] The only difference between this comparative example and Example 1 is that an equal amount of polyborosiloxane is used to replace the amino-terminated polyborosiloxane.
[0047] The refractoriness, room temperature fracture toughness, high temperature (1650°C) fracture toughness, room temperature compressive strength, high temperature (1350°C) compressive strength, room temperature flexural strength, high temperature (1500°C) flexural strength, and interface bonding strength between the composite fiber and the refractory material of the tundish permanent layer refractory materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested; Among them, the refractoriness test method refers to GB / T 7322-2017 "Test method for refractoriness of refractory materials"; The single-edge notched beam method (SENB method) was used to test the fracture toughness at room temperature and high temperature (1650°C); The test of compressive strength at room temperature refers to GB / T 5072-2023 "Test method for compressive strength of refractory materials at room temperature"; The test of high temperature compressive strength refers to GB / T 34218-2017 "Test method for high temperature compressive strength of refractory materials", and the test temperature is set to 1350℃; The test of room temperature flexural strength refers to GB / T 3001-2017 "Test method for room temperature flexural strength of refractory materials"; The test of high temperature flexural strength refers to GB / T 3002-2017 "Test method for high temperature flexural strength of refractory materials", and the test temperature is set to 1500℃; The interfacial bond strength between the composite fiber and the refractory material was measured using an Instron 3343 universal testing machine. Single-fiber pullout tests were conducted at room temperature using a 10N force transducer, with a load measurement accuracy of ±0.5% and a loading rate of 0.01 mm / s. Each group was tested 10 times, and the average value was taken. The interfacial bond strength was calculated as: maximum load at which the composite fiber was pulled out of the refractory matrix / (single fiber diameter × single fiber length × π).
[0048]
[0049] As can be seen from Table 1, the refractory materials prepared in Examples 1 to 5 have better refractory and mechanical properties than those in Comparative Examples 1 to 3.
[0050] In Comparative Example 1, amino-terminated polyborosiloxane is omitted, and its comprehensive performance is lower than that of Example 1, indicating that amino-terminated polyborosiloxane molecules contain BO bonds and Si-O bonds. These chemical bonds have high bond energies and have excellent high temperature resistance and oxidation resistance. After grafting, a protective layer can be formed on the fiber surface. During sintering and subsequent use, it can inhibit the oxidation of the carbon phase in the composite fiber and prevent the collapse of the fiber structure. At the same time, a continuous and dense protective film is formed on the fiber surface to maintain the toughening effect of the fiber. Moreover, the amino-terminated polyborosiloxane reacts, and its chain segments can reduce the agglomeration between fibers through the steric hindrance effect. The more uniform dispersion can enable the fibers to form a more effective "reinforcement network" in the refractory material, avoiding stress concentration caused by local fiber accumulation, or strength weak areas caused by local fiber loss, thereby ensuring the uniformity of material performance, which is beneficial for the fibers to exert their toughening effect and improve the fire resistance and other properties of the material.
[0051] In Comparative Example 2, PDA and amino-terminated polyborosiloxane were omitted, and the overall performance was lower than that of Example 1, indicating that polydopamine has strong adhesion and can improve the interfacial compatibility between the composite fiber and the refractory matrix (magnesium iron spinel, nano-alumina, etc.).
[0052] The polyborosiloxane in Comparative Example 3 lacks amino groups and cannot be chemically grafted with PDA. Physical mixing is the only option. This prevents the polyborosiloxane from being firmly grafted onto the PDA coating surface. During subsequent ball milling, dry pressing, and high-temperature sintering, it easily falls off due to mechanical forces or heat. This prevents the effectiveness of the modified layer throughout the entire refractory preparation process. Consequently, its overall performance is inferior to that of Example 1.
[0053] The above disclosures are only a few specific embodiments of the present invention. However, the embodiments of the present invention are not limited thereto. Any changes that can be conceived by those skilled in the art should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a permanent layer refractory material for a tundish for a short-process steelmaking process of thin strip casting and rolling, characterized in that: The following steps are involved: S1, preparing ZrO2 / carbon wrapped fibers; S2. Dissolve dopamine hydrochloride in Tris-HCl buffer (pH = 8.5), stir for 4-8 minutes, then add ZrO2 / carbon-coated fibers, soak at room temperature for 6-8 hours, wash, and dry to obtain PDA / ZrO2 / carbon-coated fibers; S3, dissolving amino-terminated polyborosiloxane in anhydrous ethanol, soaking the PDA / ZrO2 / carbon-wrapped fiber in the anhydrous ethanol for 6-8 hours, washing, and drying to obtain a composite fiber; S4. Put magnesia spinel, nano-alumina, fused chromium oxide, boron carbide, white dextrin and anhydrous ethanol into a ball mill and mix them by ball milling for 2 hours to obtain a ball-milled product; after drying the ball-milled product, mix it evenly with the composite fiber, and then dry-press it under a pressure of 15 MPa to obtain a green body; sinter the green body and cool it to room temperature to obtain the refractory material for the permanent layer of the tundish.
2. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S1, the specific preparation steps of ZrO2 / carbon-wrapped fibers are as follows: A1: Polycrystalline alumina fibers were immersed in a glucose aqueous solution with a pH of 1.5-2, transferred to an autoclave after ultrasonic treatment, sealed, and evacuated to a vacuum of 0.08 MPa. After standing for 1-2 hours, the vacuum was broken to atmospheric pressure. The autoclave was heated to 190°C at a heating rate of 2°C / min, held at that temperature for 4 hours, and then cooled to room temperature. The solid matter was separated, washed, and dried to constant weight to prepare carbon-wrapped fibers. A2: After evenly mixing anhydrous ethanol and 24wt% hydrogen peroxide, zirconium oxychloride octahydrate was added with stirring, and acetylacetone was added after continued stirring to obtain a sol treatment solution; the carbon-wrapped fiber was added into the sol treatment solution, immersed for 50-60 minutes, and the solid was separated. After drying to constant weight, the solid was transferred into a calcining furnace, and heated to 820°C at a heating rate of 4°C / min in an argon atmosphere. The fiber was kept warm and calcined for 3 hours, and then cooled to room temperature to obtain ZrO2 / carbon-wrapped fiber.
3. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 2, characterized in that: In step A1, the ratio of polycrystalline alumina fiber to glucose aqueous solution is 1 g: 80-100 mL; the mass concentration of the glucose aqueous solution is 17 wt%-20 wt%.
4. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 2, characterized in that: In step A2, the usage ratio of anhydrous ethanol, hydrogen peroxide, zirconium oxychloride octahydrate, and acetylacetone is 7 mL:50 mL:8-9 g:1.2 g; and the usage ratio of carbon-wrapped fiber to sol treatment solution is 1 g:50-60 mL.
5. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S2, the usage ratio of dopamine hydrochloride, Tris-HCl buffer, and ZrO2 / carbon-wrapped fiber is 0.1-0.2 g:100 mL:2 g.
6. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S3, the usage ratio of amino-terminated polyborosiloxane, anhydrous ethanol, and PDA / ZrO2 / carbon-wrapped fiber is 0.15-0.2 g: 80-100 mL: 2 g.
7. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S3, the preparation method of amino-terminated polyborosiloxane is: Ethyl orthosilicate, boric acid and deionized water were weighed and added to an 80% by volume ethanol aqueous solution, heated to 80°C, and dilute hydrochloric acid was added and reacted for 3 h. 3-aminopropyltrimethoxysilane was then added and reacted for 3 h. The mixture was kept warm and subjected to reduced pressure distillation to remove water and ethanol. After vacuum drying, amino-terminated polyborosiloxane was obtained.
8. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 7, characterized in that: The usage ratio of ethyl orthosilicate, boric acid, deionized water, ethanol aqueous solution, dilute hydrochloric acid, and 3-aminopropyltrimethoxysilane is 4.1 g: 0.6 g: 1-2 mL: 10 mL: 0.05 g: 2.7-3.6 g.
9. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S4, the mass ratio of magnesia spinel, nano-alumina, fused chromium oxide, boron carbide, white dextrin, anhydrous ethanol, and composite fiber is (40-48): (20-22): (10-15): (1-4): (1.5-2): (60-70): (8-12).
10. The method for preparing a tundish permanent layer refractory material for short-process steelmaking using thin strip casting and rolling according to claim 1, characterized in that: In step S4, the sintering temperature is 1250-1350° C., and the sintering time is 2-3 hours.
Citation Information
Patent Citations
A composite fiber toughened refractory material and its preparation process
CN106336228B